МЕХАНИЗМЛАРДАГИ ТАРКИБЛИ ТИШЛИ ЦИЛИНДРЛАРНИНГ ДЕФОРМАЦИЯСИДАГИ ҲОЛАТ ТАҲЛИЛИ - Мирзаев, Отабек; Боймуратов, Фаррух; Мустапақулов, Содиқ (Innovatsion texnologiyalar, 2022)
The article provides a dynamic analysis of compound gear cylinders found in mechanisms. It is known that in order to reduce the mutual deformations of the working bodies in the mechanisms and increase the productivity of the mechanisms, the installation of rubber shells on them remains one of the new areas of mechanical engineering. The problem of studying the forces arising in the study of the motion of mechanisms is one of the important directions in this area. Dynamic solutions of the problem are presented in the form of graphs. Deformation and stretching of the gear cylinder under the action of forces were developed according to the Euler equation.